EKOLOGI POLITIK DAN DINAMIKA SOSIO-EKONOMI DI DATARAN TINGGI KABUPATEN PEMALANG, JAWA TENGAH - Nur Rosyid (Research Centre for Population, Indonesian Institute of Sciences, 2015)
This paper explain the role of state in ecological aspects in the forming of socio economic dynamics in uplandÂ Pemalang District, especially in migration dynamic, the expansion and constriction of labours, and their negotiation to the ecological changes. So far, many scholars set out the demographic problems by the issues of poverty, inequality resources, increase of population, labour surplus, and so on. This causal explanation was lack in question on what kind of possibilities force those problems happened. The research has been done in the upland of Watukumpul, Pemalang, Central Java, try to understand how the upland demographical dynamics situated by political-economic and ecological forces. This area is suitable because of vast spreading in changing of farming system: from rice and glagah cultivation to cash crop of Albasia through the reforestation programs and Green campaign. By using quantitative and qualitative method and political ecology approaches. I assume that the ecological changes are forced and situated by political economic state interventions through policies and environmental condition which both farmer and state negotiation be possible. The result show, there was a changing to develop the new rural economic (new plantation) and migration pattern as a part of farmer strategies concerning to the economic opportunities and state intervention through reforestation programs. These choices imply to the changing of farmerâ€™s daily routines and their household productionÂ